A Foxtail mosaic virus Vector for Virus-Induced Gene Silencing in Maize . Issue 2 (28th April 2016) - Mei, Yu; Zhang, Chunquan; Kernodle, Bliss M.; Hill, John H.; Whitham, Steven A.
Abstract : The development of an infectious clone of Foxtail mosaic virus and demonstration of its use for virus-induced gene silencing applications in maize are described. Abstract: Plant viruses have been widely used as vectors for foreign gene expression and virus-induced gene silencing (VIGS ). A limited number of viruses have been developed into viral vectors for the purposes of gene expression or VIGS in monocotyledonous plants, and among these, the tripartite viruses Brome mosaic virus and Cucumber mosaic virus have been shown to induce VIGS in maize ( Zea mays ). We describe here a new DNA-based VIGS system derived from Foxtail mosaic virus (FoMV ), a monopartite virus that is able to establish systemic infection and silencing of endogenous maize genes homologous to gene fragments inserted into the FoMV genome. To demonstrate VIGS applications of this FoMV vector system, four genes, phytoene desaturase (functions in carotenoid biosynthesis), lesion mimic22 (encodes a key enzyme of the porphyrin pathway), iojap (functions in plastid development), and brown midrib3 (caffeic acid O -methyltransferase), were silenced and characterized in the sweet corn line Golden × Bantam. Furthermore, we demonstrate that the FoMV infectious clone establishes systemic infection in maize inbred lines, sorghum ( Sorghum bicolor ), and green foxtail ( Setaria viridis ), indicating the potential wide applications of this viral vector system for functional genomics studies in maize and other monocots.